2021
DOI: 10.1080/02670844.2021.1900518
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tool materials on surface modification using μEDC process

Abstract: The work aims to assess the influence of tool electrode material while surface modification of Tialloy through the micro-electrical discharge coating (μEDC) process. Brass and tungsten microtool (800 μm)are chosen based on their mechanical, thermal, and electrical properties to conduct the experiments at different coating criteria such as duty cycle, voltage, and powder (tungsten disulphide) concentration. Various performance indexes i.e., micro-hardness, surface roughness, and recast surface height, are evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It is found 27% reduction in EW as compared to EDM of the same material without electrode cooling as pulse off-time and voltage increase to their highest values of 6 μ and 24 V respectively. Shirguppikar et al [24] studied the effect of thin-film titanium nitride (TiN) coating on tungsten carbide (WC) micro-electrode on TWR, overcut, and depth of machining in micro-drilling of Ti-6Al-4 V. The experimental findings showed that as compared to an uncoated micro-tool electrode, TWR fell by 16. 32 percent, depth of machining increased by 20.…”
Section: Titanium Alloy and Cutting Tool Materialsmentioning
confidence: 99%
“…It is found 27% reduction in EW as compared to EDM of the same material without electrode cooling as pulse off-time and voltage increase to their highest values of 6 μ and 24 V respectively. Shirguppikar et al [24] studied the effect of thin-film titanium nitride (TiN) coating on tungsten carbide (WC) micro-electrode on TWR, overcut, and depth of machining in micro-drilling of Ti-6Al-4 V. The experimental findings showed that as compared to an uncoated micro-tool electrode, TWR fell by 16. 32 percent, depth of machining increased by 20.…”
Section: Titanium Alloy and Cutting Tool Materialsmentioning
confidence: 99%
“…The FESEM images of some samples are shown in Figure 10. The high temperature (8,000-20,000°C) at the electrode gap [26], leads to melting and evaporation of electrodes materials [27]. The dielectric fluid does the action of rapid cooling of the molten material thereby it induces micro cracks, craters, globules, and voids in the modified surface.…”
Section: Fesem and Eds Analysismentioning
confidence: 99%
“…They reported that carbon with high concentrations reduces the formation of microcracks, minimize the surface roughness, and improves the hardness of layer. While in other studies the impact of electrode in modification of Ti-alloy surface is investigated through the micro-EDC [7]. Tyagi et al coated on mild steel substrate using solid-lubricant of MoS 2 and Cu powder by EDC technique and studied the surface integrity and tribological characteristics of the coated surface [8].…”
Section: Introductionmentioning
confidence: 99%